Synergies and trade-offs between biodiversity and distance to settlements in the spatial allocation of wind power - Luukkonen, Saara; Räsänen, Aleksi; Koivula, Matti; Tolvanen, Anne (Academic Press, 2026)
The need to phase out fossil energy has promoted a rapid development of wind power, yet this development may negatively affect biodiversity and encounter resistance among local citizens. To study whether optimal locations for wind power differ when considering biodiversity impacts or distance to settlements, we used spatial suitability analysis for allocating wind power in Pirkanmaa region in southern Finland. We clustered high-suitability areas using Anselin Local Moran's I cluster analysis to find spatially contiguous areas for wind power. We compared the results of biodiversity-based and settlement-based allocation in three scenarios for electricity production for the year 2035: the Minimum scenario corresponded to the current production-consumption ratio in the region, the Self-sufficiency scenario to regional electricity self-sufficiency, and the Maximum scenario to the maximum production capacity. The most suitable locations for wind power were forested areas in the sparsely populated parts of the region. Optimal locations for biodiversity-based and settlement-based suitability showed only partial overlap, suggesting trade-offs in wind power allocation. The overlap area increased from 0% in the Minimum scenario to 41% in the Maximum scenario. The total area of the highly suitable locations based on both biodiversity and distance to settlements was not sufficient to cover the production capacity in the Self-sufficiency scenario, indicating that reaching electricity self-sufficiency may not be possible without compromising biodiversity or distance to settlements. The results highlight the importance of considering both biodiversity values and human well-being in wind power development, as potential for conflicts in wind power development is likely to increase with growing electricity demand in the future.
Keywords: multi-criteria decision analysis; MCDA; renewable energy; multi-criteria optimization; suitability analysis; land use planning; analytic hierarchy process; AHP